2023
DOI: 10.2196/40330
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Technology to Support Health Care Professionals and Family Caregivers Caring for Patients With Cognitive Impairment: Scoping Review

Abstract: Background Digital health technology is a promising way of supporting health care providers and family caregivers as they care for patients with cognitive impairment. Objective This scoping review aimed to portray the use of digital health technology to assist health care providers and family caregivers in caring for patients with cognitive impairment who live in the community or in a facility. Methods We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Several frameworks highlighted the role of specific built environmental features, such as outdoor nature-based activity [40 ▪▪ ,41 ▪ ], community-integrated long-term care and housing options [42 ▪▪ ,43 ▪▪ ,44 ▪ ], or regional influences [45 ▪ ,46 ▪ ,47,48 ▪ ,49 ▪▪ ,50 ▪ ,51 ▪ ]. Others focused on the arts, digital technologies, and other cognitive stimuli in community settings [52 ▪ ,53 ▪▪ ,54 ▪ ,55 ▪ ,56 ▪ ].…”
Section: Resultsmentioning
confidence: 99%
“…Several frameworks highlighted the role of specific built environmental features, such as outdoor nature-based activity [40 ▪▪ ,41 ▪ ], community-integrated long-term care and housing options [42 ▪▪ ,43 ▪▪ ,44 ▪ ], or regional influences [45 ▪ ,46 ▪ ,47,48 ▪ ,49 ▪▪ ,50 ▪ ,51 ▪ ]. Others focused on the arts, digital technologies, and other cognitive stimuli in community settings [52 ▪ ,53 ▪▪ ,54 ▪ ,55 ▪ ,56 ▪ ].…”
Section: Resultsmentioning
confidence: 99%
“…Delving into other characteristics of any educational experience, such as the role of the educational community and the collaboration of families, it should be noted that these variables have not been considered in the studies found. In general, families appear involved in studies referring to social robots when these are used as support in the home (Gasteiger et al, 2021;Choukou et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…We must bear in mind that the latter is characterized as being technological, which highlights the need to address the exploitation of any possibility related to digital technology (Roig-Vila et al, 2021;Alonso Ruiz et al, 2022;Cabezas-González et al, 2022). In fact, even though some experiences associated with social robotics can be found in various fields (Lau et al, 2020;Gasteiger et al, 2021;Choukou et al, 2023), a priori, education does not seem to be one of them.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has presented a real training ground in this field and an unexpected growth stimulus never experienced before, with the consolidation of ancient areas and the exploration of new areas. Furthermore, even in TH and DH, one can currently count on the use of emerging technologies, such as robotics [ 24 , 25 , 26 , 27 ], augmented reality [ 28 ], virtual reality [ 29 ], and artificial intelligence [ 30 , 31 ]. Moreover, assistive technologies have played a strategic role during the pandemic as they were consolidated in the context of different applications and disabilities relating communication and motion [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: The Impact Of Covid-19 In This Fieldmentioning
confidence: 99%
“…Big Data have played a strategic role in overcoming the pandemic [ 52 ]. Assistance for the disabled has tested new solutions [ 24 , 25 , 26 , 27 ], such as the social robot, which has played an innovative role as a support and/or mediator between a therapist and a patient [ 24 , 25 , 27 ]. In this case, the therapist have experienced a radical change in their role.…”
Section: The Impact Of Covid-19 In This Fieldmentioning
confidence: 99%